ASSESSMENT OF PERIODONTAL HEALTH STATUS OF CHRONIC KIDNEY DISEASE PATIENTS UNDERGOING HEMODIALYSIS; A CROSS SECTIONAL DESCRIPTIVE STUDY - Arsalan Wahid; Saima Chaudhry; Muhammad Arshad Badar (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To assess the periodontal health status of Chronic Kidney Disease patients on maintenance hemodialysis therapy STUDY DESIGN: Cross Sectional Descriptive Study STUDY SETTINGS: National Institute of Kidney Diseases (NIKD), Shaikh Zayed Medical Complex, Lahore MATERIALS & METHODS: One sixty (160) patients undergoing maintenance hemodialysis therapy were enrolled for the study on the basis of inclusion/exclusion criteria. Their demographic, medical and periodontal parameters were assessed using UNC-12 periodontal probe and findings were recorded on a structured Performa. RESULTS: The mean age of patients was 41.37 ± 12.47 and the male female ratio was 10/6. Majority of the patients (72.5%) were having education metric or below, 69% patients were not able to work due to their disease status. 79% patients were hypertensive and 59% patients were not getting dialysis according to international nephrology guidelines (thrice a week). Regarding periodontal status, three parameters BOP (60.5 ± 21.9) PPD (2.0 ± 0.41) and CAL (2.4 ± 0.9) were assessed which are reliable indicators of periodontal health. PPD and CAL were also categorized in 4mm and 3mm categories. PPD sites ≥ 4mm (3.1 ±5.6) and CAL Sites ≥ 3mm (22.6 ± 11.8). Statistical analysis revealed significant association between hemoglobin, creatinine, albumin and periodontal parameters (PPD, CAL, BOP). CONCLUSION: Periodontal health of CKD patients on maintenance dialysis therapy was poor and it might be a factor in the poor prognosis of their kidney disease due to increased systemic inflammatory burden of periodontal diseases. Oral health awareness campaign must be an integral part of hemodialysis therapy to get a better prognosis.